Rediscovering The Core Cognitive Processes That Define Scientific Competence. - Embeywa, Henry E. (Machakos University Press, 2019)
Scientific competence has largely been portrayed in terms of observable attributes like: observation, classification, experimentation, problem-solving, explanation among others. This conceptualization ignores the cognitive processes involved in the construction and assessment of scientific knowledge. This paper argues that the greater focus should be on the justification of the central cognitive processes if scientific competence is to be the goal of any science curriculum.
Keywords: Scientific; competence; core; cognitive; process; construction; assessment